Analysis of T cell responses to the major allergens from German cockroach: epitope specificity and relationship to IgE production() - Oseroff, Carla (2012)
Bla g allergens are major targets of IgE responses associated with cockroach allergies. However, little is known about corresponding T cell responses, despite their potential involvement in immunopathology and the clinical efficacy of Specific ImmunoTherapy (SIT). Bioinformatic predictions of the capacity of Bla g 1, 2, 4, 5, 6, and 7 peptides to bind HLA DR, DP and DQ molecules, and PBMC responses from 30 allergic donors, identified 25 T cell epitopes. Five immunodominant epitopes accounted for over half of the response. Bla g 5, the most dominant allergen, accounted for 65% of the response, and Bla g 6 accounted for 20%. Bla g 5 induced both IL-5 and IFN-γ responses, while Bla g 6 induced mostly IL-5 and, conversely, Bla g 2 induced only IFN-γ. Thus, responses to allergens within a source are independently regulated, suggesting a critical role for the allergen itself, and not extraneous stimulation from other allergens or co-presented immunomodulators. In comparing antibody with T cell responses for several donor/allergen combinations we detected IgE titers in the absence of detectable T cell responses, suggesting that unlinked T-B help might support development of IgE responses. Finally, SIT resulted in IL-5 down-modulation, which was not associated with development of IFN-γ or IL-10 responses to any of the Bla g derived peptides. In summary, the characteristics of T cell responses to Bla g allergens appear uncorrelated with IgE responses. Monitoring these responses may therefore yield important information relevant to understanding cockroach allergies and their treatment.